Bases teórico-conceituais e subsídios para a classificação hidrogeomorfológica das áreas úmidas em Minas Gerais - Cecilia Siman Gomes (2016)
Wetlands are considered one of the most important ecosystems. They cover nearly 20% of brazilian territory but their functions and benefits are still poorly known and recognized. Brazil became a member of Ramsars Convention in 1993, but advanced slowly to establish criteria for definition, classification and delimitation necessary to warrant protection and sustainable use of its wetlands. Classification systems are essential in these processes since they provide categorization, conceptual and terminological uniformity. The hydrogeomorphic (HGM) parameters have been widely recognized and used in the first levels of classification, characterizing wetlands according to their geomorphological context and hydrology dynamics, as well as increasing the understanding of their environmental functions. In the state of Minas Gerais the diversity of morphologies condition a variety of types of wetlands. In this context, this research aimed to develop a conceptual reference proposal and define hydrogeomorphological classes to provide subsidies to compose the first levels of a classification system for wetlands in Minas Gerais, seeking to contribute to its protection and management and future scientific research in the area. During the research, studies of conceptual and institutional wetlands references, studies of several classification systems (including the case of the HGM South African System) and interviews with wetlands scientists were done. Several tables of analysis and synthesis combining results of these studies and interviews enabled a greater articulation of this research. The proposal resulted in a conceptual synthesis that includes characteristics related to the formation, identification, and delimitation of wetlands, looking for greater agreement by various professionals and their application in the field. For Minas Gerais, five major wetlands HGM Classes were proposed, namely: Floodplain Wetlands; Depression Wetlands; Wetlands High Flats; Seep Wetlands; and Valley-bottom Wetlands (with any or few depositional features). Each of these five configurations shows morphological and hydrological dominant characteristic, together with the wet system and main types of superficial covers associated. An initial overview of wetland class distribution in Minas Gerais was elaborated. These prepositions may contribute to future researches and to the development of more effective tools for protection and wise use of these kind of systems.